2012
DOI: 10.4236/jbise.2012.52006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and <i>in vitro</i> antibacterial evaluation of some thiosemicarbazides and thiosemicarbazones

Abstract: In the present study various thiosemicarbazides and thiosemicarbazones were synthesized and screened for their antimicrobial activity. Among the ligands tested, compounds 1, 3, 4 and 5 demonstrated inhibitory effects at 0.4 - 0.5 µM concentrations against <i>E. coli</i> while 1-(4-fluorobenzoyl)-N4-ethyl-thiosemicar-bazide (3) demonstrated the maximum inhibitory effective compound against <i>E. coli</i>, also possessing high water solubility. Instead, compound 3 demonstrated weak antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The thiosemicarbazide derivatives 1 and 2 substituted with aliphatic substituents: ethyl (1) and allyl (2) as well as compound 4 substituted with meta-methoxyphenyl showed the strongest activity among all of synthesized compounds. Ortho-methoxyphenyl and para-methoxyphenyl thiosemicarbazide derivatives (3,5) showed the weakest activity among all thiosemicarbazide derivatives. In the case of thiosemicarbazide (6) and 1,2,4-triazole derivative (12), the presence of 4-ethoxyphenyl substituent can be connected with the lack of antimicrobial activity.…”
Section: Structure-activity Relationshipmentioning
confidence: 97%
See 3 more Smart Citations
“…The thiosemicarbazide derivatives 1 and 2 substituted with aliphatic substituents: ethyl (1) and allyl (2) as well as compound 4 substituted with meta-methoxyphenyl showed the strongest activity among all of synthesized compounds. Ortho-methoxyphenyl and para-methoxyphenyl thiosemicarbazide derivatives (3,5) showed the weakest activity among all thiosemicarbazide derivatives. In the case of thiosemicarbazide (6) and 1,2,4-triazole derivative (12), the presence of 4-ethoxyphenyl substituent can be connected with the lack of antimicrobial activity.…”
Section: Structure-activity Relationshipmentioning
confidence: 97%
“…1,2,4-Triazole derivatives (7)(8)(9)(10)(11)(12) were prepared in twostep synthesis. In the first step of synthesis, 3-hydroxy-2-naphthoic hydrazide was subjected to condensation reaction with appropriate isothiocyanates to afford 1,4-disubstituted thiosemicarbazide derivatives (1)(2)(3)(4)(5)(6). Then new 1,2,4-triazole-3-thiones (7)(8)(9)(10)(11)(12) were synthesized by the cyclization reaction of corresponding thiosemicarbazide (1-6) derivatives in alkaline media.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, literature survey revealed that thiosemicarbazones constitute one of the most versatile classes of compounds possessing antimicrobial and anti-amoebic activities [16][17][18][19][20] , depending on the nature of the substituents at N 1 and N 4 of thiosemicarbazone moiety. Various thiosemicarbazone derivatives have been successfully developed and documented as antimicrobial agents [16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%